Iron Death Regulatory Network: Expression Characterization and Prognostic Correlation Study of ARL6IP1 in Colorectal Cancer - Liu, Guancheng; Liu, Shichao; Bordunov, Jiatai Guo; Bordunov, Rui Zhang (Trends in Immunotherapy, 2025)
This study leveraged publicly available databases, including The Cancer Genome Atlas (TCGA) and the Gene Expression Omnibus (GEO), to investigate the expression patterns of ARL6IP1 in colorectal cancer (CRC) and its prognostic relevance. The results demonstrated that reduced ARL6IP1 expression is strongly associated with poorer overall survival (OS), disease-specific survival (DSS), and progression-free survival (PFS) in CRC patients, establishing ARL6IP1 as an independent prognostic marker for CRC. Further analyses using Gene Set Enrichment Analysis (GSEA) and Protein-Protein Interaction (PPI) network investigations indicated that low ARL6IP1 expression is enriched in cancer-related signaling pathways, suggesting its involvement in CRC pathogenesis through the ferroptosis mechanism. Additionally, the study uncovered a correlation between ARL6IP1 expression and immune cell infiltration within the tumor microenvironment (TME), particularly immunosuppressive cell populations such as regulatory T cells (Tregs) and M2-type macrophages. Diminished ARL6IP1 levels may promote the development of an immunosuppressive TME, thereby aiding tumor immune evasion. Collectively, these findings highlight ARL6IP1 as a critical ferroptosis-related gene that may significantly influence CRC progression and immune escape, offering a potential target for prognostic evaluation and therapeutic intervention in CRC. This study aims to investigate the expression patterns of ARL6IP1 in colorectal cancer (CRC) and its prognostic significance, as well as its correlation with immune cell infiltration in the tumor microenvironment. By leveraging publicly available databases, we sought to determine whether ARL6IP1 could serve as a potential prognostic biomarker and therapeutic target for CRC.